Juridical Analysis of the Office Term of Legislative Members in the Republic of Indonesia: ANALISIS YURIDIS TERHADAP MASA JABATAN ANGGOTA LEGISLATIF DI REPUBLIK INDONESIA - Mohamad Qudrat Malapu (IHSA Institute, 2022)
The New Order has taught us that unrestricted terms of office tend to be corrupt and used to retain power. The absence of term limits for legislative members of the House of Representatives allows incumbents to re-sit in the House of Representatives for more than 10 years or 2 terms of office, making the legislature a potentially corrupt institution. This study aims to examine the ideal term of office for legislative members (DPR) in the Republic of Indonesia to realize a healthy democracy. The analysis method is normative legal research with a statute approach and a conceptual approach.with the conclusion that Article 76, paragraph 4, of Law Number 17 Year 2014 concerning MPR, DPR, DPD, and DPRD needs to be revised by adding the phrase